Deepfake Pornografi: Tren Kekerasan Gender Berbasis Online (KGBO) Di Era Pandemi Covid-19 - Ivana Dewi Kasita (Jurnal Wanita dan Keluarga, 2022)
The development of artificial intelligence (AI) sophistication triggered a specific algorithm called deepfake technology. The existence of this technology provides convenience for workers of the television and film industry during the Covid-19 pandemic. But on the other hand, deepfake technology is used to disseminate pornographic content until cases of Online Gender Based Violence (OGBV) during the Covid-19 pandemic increase dramatically. based on the data, this study aims to describe what exactly are the dangers of deepfake technology in the spread of OGBV and how the government's efforts in dealing with pornography deepfake cases. The research method used is a method of literature study with qualitative descriptive analysis. The results showed that the dangers of deepfake pornography are various, such as victims experiencing trauma, loss of self-esteem, dignity and various forms of stigma obtained from social environments that do not support victims to get justice. Therefore, in the face of the development of deepfake technology the government can make efforts by strengthening regulations related to the protection of personal data, handling, recovery of victims of gender violence due to deepfake pornography, and conducting education both law enforcement officials and the public regarding the dangers of deepfake technology.